The process of an intercountry adoption : the role of the women within the couples involved : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University - Wilson, Catherine Marie (Massey University, 2001)
This thesis studies the experiences of ten married couples in New Zealand, in particular the women, who have completed the process of adopting a child or children from overseas. It has two main objectives: first to highlight the role of the woman within a married couple applying to adopt intercountry; and second, to note any gender differences in the experience and perception of this process and the issues involved. The research design for this study followed the approach of eidetic phenomenology which focuses on the perceptions and meanings that people use to interpret their own experiences. Data were collected using in-depth, audiotaped personal interviews with the participants, and detailed case notes made during the interview. Personal observations after each interview were also used. The data were analysed using content analysis with cross-case groupings of responses into themes. The findings indicate that women are the main instigators and organisers in the process of achieving an intercountry adoption. Within this role the women often felt unsupported by both professionals and organisations involved. The findings also indicate areas for further research and review for professional practice and policy, in order to provide more effective and supportive assistance throughout the process of adopting a child or children from overseas.
Keywords: Adoption, New Zealand; Interracial adoption; Intercountry adoption; Overseas adoption